Effect of preparation design on marginal and internal adaptation of translucent zirconia laminate veneers. (5th October 2018) - Kusaba, Kosuke; Komine, Futoshi; Honda, Junichi; Kubochi, Kei; Matsumura, Hideo
Abstract : This study investigated the effect of preparation design on the marginal and internal adaptation of laminate veneers (LVs) fabricated from translucent zirconia. Thirty‐three resin teeth were prepared for LVs of three designs: window preparation (WP); incisal shoulder preparation (ISP); and incisal palatal chamfer preparation (IPP). Marginal adaptation was evaluated by measuring the vertical discrepancy between the LV margin and the finish line at 60 points. The internal adaptation was assessed by measuring the internal space width as the distance between the LV and the tooth at cervical, central, and incisal sites after sectioning. At the incisal, mesial, and distal sites, mean marginal discrepancies were significantly lower in the WP group than in the other two groups; the IPP group had the highest marginal discrepancies. At incisal sites, the median internal space was significantly higher in the IPP group than in the WP and ISP groups and higher in the ISP group than in the WP group. At the incisal site, marginal and internal adaptations were better for the non‐overlap translucent zirconia LV design (WP) than for the overlap designs (ISP and IPP). The characteristics of the translucent zirconia LVs used in the present study indicate acceptable clinical performance.